Production management within the concept of digital enterprises of wood-processing and furniture production - Gordana Matičević (University of Zagreb, Faculty of Forestry and Wood Technology, 2008)
Wood processing and furniture production represent a big chance for Croatia to enter the international market. Besides the natural advantages such as world-class quality of wood, Croatia also has the tradition, experience and current technological knowledge in production of semi-manufactured products and final products. Inorder to enter and survive at the competitive international market it is necessary to increase the level of logistics support for production preparation and production in order to increase the use of wood and wood material, to decrease time loss during development and acceptance of the new product and during production preparation, and especially to decrease time required for production. This paper deals with the results achieved during the development and application of the production management system that was based on theoretical principles of JIT (Just In Time) and MRPII Manufacturing Resource Planning) Japanese and American production theory and integrated in ERP (Enterprise Resource Planning) system in wood processing and furniture production enterprises. In this way, the prerequisites are created for the development of the digital enterprise in wood processing and furniture production.